Pathophysiology of ADHD and associated problems—starting points for NF interventions? - Albrecht, Björn; Uebel-von Sandersleben, Henrik; Gevensleben, Holger; Rothenberger, Aribert (Frontiers in Human Neuroscience, 2015)
Attention deficit hyperactivity disorder (ADHD) is characterized by severe and age-inappropriate levels of hyperactivity, impulsivity and inattention. ADHD is a heterogeneous disorder, and the majority of patients show comorbid or associated problems from other psychiatric disorders. Also, ADHD is associated with cognitive and motivational problems as well as resting-state abnormalities, associated with impaired brain activity in distinct neuronal networks. This needs to be considered in a multimodal treatment, of which neurofeedback may be a promising component. During neurofeedback, specific brain activity is fed-back using visual or auditory signals, allowing the participants to gain control over these otherwise unaware neuronal processes. Neurofeedback may be used to directly improve underlying neuronal deficits, and/or to establish more general self-regulatory skills that may be used to compensate behavioural difficulties. The current manuscript describes pathophysiological characteristics of ADHD, heterogeneity of ADHD subtypes and gender differences, as well as frequently associated behavioural problems such as oppositional defiant/conduct or tic disorder. It is discussed how neurofeedback may be helpful as a treatment approach within these contexts.